New amide linked dimeric 1, 2, 3-triazoles bearing aryloxy scaffolds as a potent antiproliferative agents and EGFR tyrosine kinase phosphorylation inhibitors. Issue 19 (1st October 2019) - Deshmukh, Tejshri R.; Sarkate, Aniket P.; Lokwani, Deepak K.; Tiwari, Shailee V.; Azad, Rajaram; Shingate, Bapurao B.
Graphical abstract: Highlights: We have synthesized new amide linked dimeric 1, 2, 3-triazoles bearing aryloxy scaffolds via click chemistry approach. The synthesized compounds were screened for their in vitro antiproliferative activities against MCF-7 and A-549 cell line. The compounds, 7d, 7e, 7h, 7i and 7j have revealed promising antiproliferative activities against MCF-7. The compounds, 7a, 7b, 7c, 7i and 7j were observed as potent antiproliferative agents against A-549. The compounds, 7d, 7h and 7j were acts as active EGFR tyrosine kinase phosphorylation inhibitors. Abstract: A search for potent antiproliferative agents has prompted to design and synthesize aryloxy bridged and amide linked dimeric 1, 2, 3-triazoles (7a –j ) by using 1, 3-dipolar cycloaddition reaction between 2-azido- N -phenylacetamides (4a –e ) and bis(prop-2-yn-1-yloxy)benzenes (6a –b ) via copper (I)-catalyzed click chemistry approach with good to excellent yields. All the newly synthesized compounds have been screened for their in vitro antiproliferative activities against two human cancer cell lines. The compounds 7d, 7e, 7h, 7i and 7j have revealed promising antiproliferative activity against human breast cancer cell line (MCF-7), whereas, the compounds 7a, 7b, 7c, 7i and 7j were observed as potent antiproliferative agents against human lung cancer cell line (A-549). The active compounds against MCF-7 have been also analysed for their mechanism of action by the enzymatic study, which shows that the compounds 7d, 7h and 7j were acts as active EGFR tyrosine kinase phosphorylation inhibitors. In support to this biological study, the molecular docking as well as in silico ADME properties of all the newly synthesized hybrids were predicted.